PENGARUH TIME BUDGET PRESSURE, TENUR AUDIT, DAN ROTASI AUDIT TERHADAP KUALITAS AUDIT (Studi Kasus pada Kantor Akutan Publik di Tangerang, Tangerang Selatan, dan Jakarta Barat) - Taufik Akbar (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
The problem of audit quality of auditor in Indonesia public accountant firm is there are some cases about auditor complicity to error and fraud in company financial report and cases about freezing of public accountant firm because offence against auditing standard in Indonesia i.e. SPAP in conducting an audit. The purpose of this study is to examine whether time budget pressure, audit tenure, audit rotation affect the audit quality. The population in this study consist of auditor in Tangerang, South Tangerang and West Jakarta public accountant firm. Sampling method used is simple random sampling. In this research, the total of sample is 46. Type of data used was primary data obtained from result of questionnaire answer by sample. Smart Partial Least Square (SmartPLS) path modeling method used to be analysis method. The result of this study show that time budget pressure has negative and no significant influenced of audit quality however audit tenure and audit rotation have positive and significant influenced of audit quality.